2019
DOI: 10.1186/s41938-019-0191-z
|View full text |Cite
|
Sign up to set email alerts
|

Potential activities of Bacillus simplex as a biocontrol agent against root rot of Nigella sativa caused by Fusarium camptoceras

Abstract: This study aimed to investigate the impact of two isolates of Bacillus simplex (PHYB1 and PHYB9) for controlling the root rot disease of black cumin (Nigella sativa) caused by Fusarium camptoceras (PHYF1) under greenhouse and field conditions at Assiut Governorate, Egypt. The highest reduction percentage of infection (22.5%) was recorded by the treatment of PHYB1 as suspension than the control (60%). Both isolates of Bacillus spp. provided the root and foliar dry weight under greenhouse and seed production in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…This study was of particular interest, as it demonstrated the combined antimicrobial and plant-growth-promoting effects of P. simplex isolate 30N-5 in pea (Tables 2 and 3), suggesting that such a combined activity could be more effective under field conditions [53]. Similar results were observed for isolates PHYB1 and PHYB9 in black cumin treatment [54]. Regarding the mode of action, in silico genomic studies indicated the presence of genes involved in the chitin degradation pathway and hydrolytic enzyme production, as well as cell-wall-degrading enzymes such as cellulase, pectinase, and xylanase, all of which are indicators for P. simplex's antimicrobial activity [17].…”
Section: Antimicrobial Activitysupporting
confidence: 73%
See 2 more Smart Citations
“…This study was of particular interest, as it demonstrated the combined antimicrobial and plant-growth-promoting effects of P. simplex isolate 30N-5 in pea (Tables 2 and 3), suggesting that such a combined activity could be more effective under field conditions [53]. Similar results were observed for isolates PHYB1 and PHYB9 in black cumin treatment [54]. Regarding the mode of action, in silico genomic studies indicated the presence of genes involved in the chitin degradation pathway and hydrolytic enzyme production, as well as cell-wall-degrading enzymes such as cellulase, pectinase, and xylanase, all of which are indicators for P. simplex's antimicrobial activity [17].…”
Section: Antimicrobial Activitysupporting
confidence: 73%
“…In vitro assays showed up to a 70% growth inhibition of the plant pest and fungal hyphal thinning [17,53,63], however, compared to B. subtilis, the effects were slightly lower [17]. In planta experiments further confirmed these antifungal properties, greatly reducing dis-ease severity after P. simplex application to the root seedlings of row crops or in black cumin [54,63]. The authors cautioned, however, that the results obtained from in vivo and in vitro antagonistic assays were not always aligned [63], and thus appropriate care should be taken for the screening of biocontrol agents under field conditions.…”
Section: Antimicrobial Activitymentioning
confidence: 83%
See 1 more Smart Citation
“…For example, we identify a significant peak of association in the A07p36280.1_BnaRCC gene (encoding a deoxyribonucleoside kinase: ATDNK) to be associated with bacterial species richness (Dataset S11, S12). Interestingly, we found a significant peak on chromosome 9 to be associated with the bacterial species Bacillus simplex (Dataset S11, S12) described to be a biocontrol agent against Fusarium fungal pathogens and other plant pathogens as most Bacillus species (19, 20). The peak fell in the A09p41890.1_BnaRCC gene, whose A. thaliana ortholog correspond to the TIP41-like protein that was shown to be involved in the plant defense against bacterial pathogens (21).…”
Section: Resultsmentioning
confidence: 93%